Juries in capital cases - Hans, Valerie P. (The Elgar companion to capital punishment and society, 2024)
The United States is one of the few countries in the world to rely on juries composed of lay citizens to decide the guilt and punishment of defendants facing the death penalty. The death penalty context presents multiple challenges, including selecting individuals whose views permit them to either convict or acquit and recommend life or death, based solely on the evidence presented at trial. Compared to individuals who disapprove of capital punishment, these so-called death-qualified jurors bring a biased perspective to interpreting evidence of guilt, aggravation, and mitigation. These problems are exacerbated when fewer citizens support capital punishment. Despite this, juries are reliably less likely to convict and sentence to death compared to judges. This chapter discusses this counterintuitive finding after reviewing procedures in US capital cases and decision-making processes of capital jurors. It also examines alternative approaches used in other countries, including decision-making by judges and mixed tribunals.